Репрезентативність дендросозоекзотів заповідних садово-паркових об’єктів зони широколистяних лісів України - Міськевич, Лариса; Miskevych, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2017)
Проаналізовано видову, категоріальну та об’єктну репрезентативність. Установлено, що переважна кількість видів дендросозоекзотів зосереджена в ботанічних садах і дендропарках. Означено найрепрезентативніші штучні заповідні парки за кількістю раритетних видів екзотичних рослин. Найрепрезентативнішими виявилися Thuja occidentalis L., Larix decidua L., Aesculus hippocastanum L. і Robinia pseudoacacia L. Here we considered representativeness of cultivation in artificial dendrosozoexotics of the protected landscape and gardening objects of the broadleaf forests zone of Ukraine. We presented the list of the most widespread of rare dendrosozoexots. The most presented are: Thuja occidentalis L., Larix decidua L. and Aesculus hippocastanum L. and Robinia pseudoacacia L. Coniferous woody plants are dominated of the total number of rare dendroexots. In this article we defined categories and objects of natural reserve fund, territories of greatest dendrosozoexotics which are the most protected. It was found that a significant number of species represented in the botanical gardens and arboretums. It is established that the greatest number of rare species of dendroexots are presented in botanical gardens and arboretums. On the territories of botanical gardens protected 98 species, dendrological parks represented 74 species. The largest number of dendrosozoexotics (60 species)concentrated in Ivan Franko’s Botanical Garden of the National University of Lviv. The parks-monuments of landscape architecture represented as 46 rare species of dendroexots. Presented list of artificial protected parks, which are the most representative of the number of rare species.
Representativeness of Dendrosozoexotics of the Protected Landscape Gardening Objects of the Broadleaf Forests Zone of Ukraine.
Keywords: репрезентативність; категорія природно- заповідного фонду; штучні заповідні парки; дендросозоекзоти; representation; category of natural reserve fund; artificial protected parks; dendrosozoekzoty